La Noble Science des Joueurs d’Espée: Fight Book and Commercial Product - Mathijs Roelofsen (Acta Periodica Duellatorum)
La Noble Science des Joueurs d’Espée (originally La Noble Science des Ioueurs Despee) is a fight book printed in 1538 by Willem Vorsterman, a local printer in Antwerp. Printed in several exemplars, the book is the French translation of a German fencing treatise written by Andre Paurnfeindt, which itself was first published in Vienna in 1516. The study of Vorsterman’s edition shows several errors were made in recreating Paurnfeindt’s work, including inversions of image and text, which have the potential to alter the transmission of the text’s martial knowledge. This raises the question of Vorsterman's commercial intentions when editing and printing this fight book, especially regarding the flourishing printing business in sixteenth-century Flanders. This paper aims to describe the differences in construction between Vorsterman and Pauernfeindt’s treatises in the context of both printing and martial cultures in Antwerp and the surrounding region.